Randomized Trial of Simple Versus Complex Drug-Eluting Stenting for Bifurcation Lesions: The British Bifurcation Coronary Study: Old, New, and Evolving Strategies - Hildick-Smith, David; de Belder, Adam J.; Cooter, Nina; Curzen, Nicholas P.; Clayton, Tim C.; Oldroyd, Keith G.; Bennett, Lorraine; Holmberg, Steve; Cotton, James M.; Glennon, Peter E.; Thomas, Martyn R.; MacCarthy, Philip A.; et al. (Circulation (New York, N.Y.), 2010)
Background— The optimal strategy for treating coronary bifurcation lesions remains a subject of debate. With bare-metal stents, single-stent approaches appear to be superior to systematic 2-stent strategies. Drug-eluting stents, however, have low rates of restenosis and might offer improved outcomes with complex stenting techniques. Methods and Results— Patients with significant coronary bifurcation lesions were randomized to either a simple or complex stenting strategy with drug-eluting stents. In the simple strategy, the main vessel was stented, followed by optional kissing balloon dilatation/T-stent. In the complex strategy, both vessels were systematically stented (culotte or crush techniques) with mandatory kissing balloon dilatation. Five hundred patients 64±10 years old were randomized; 77% were male. Eighty-two percent of lesions were true bifurcations (>50% narrowing in both vessels). In the simple group (n=250), 66 patients (26%) had kissing balloons in addition to main-vessel stenting, and 7 (3%) had T stenting. In the complex group (n=250), 89% of culotte (n=75) and 72% of crush (n=169) cases were completed successfully with final kissing balloon inflations. The primary end point (a composite at 9 months of death, myocardial infarction, and target-vessel failure) occurred in 8.0% of the simple group versus 15.2% of the complex group (hazard ratio 2.02, 95% confidence interval 1.17 to 3.47, P =0.009). Myocardial infarction occurred in 3.6% versus 11.2%, respectively ( P =0.001), and in-hospital major adverse cardiovascular events occurred in 2.0% versus 8.0% ( P =0.002), respectively. Procedure duration and x-ray dose favored the simple approach. Conclusions— When coronary bifurcation lesions are treated, a systematic 2-stent technique results in higher rates of in-hospital and 9-month major adverse cardiovascular events. This difference is largely driven by periprocedural myocardial infarction. Procedure duration is longer, and x-ray dose is higher. The provisional technique should remain the preferred strategy in the majority of cases. Clinical Trial Registration Information— URL: http://www.clinicaltrials.gov. Unique identifier: NCT 00351260.